Relação entre o resultado do jogo e os desempenhos técnico e tático individual de uma seleção (2018-2019) - Denis, Ricardo Silva (2021)
Football attracts thousands of people around the world, since it is considered one of the biggest sports in participation and public. A sport characterized by being an acyclic modality and intermittent efforts of high intensity and short duration, football requires at all times that its athletes are able to do the best performance in all the factors required throughout the match, to achieve victory in the matches and in the championships that are playing. In order to do that, it is extremely important to have knowledge about the impact of performance indicators played by athletes on the outcome of matches. Thus, the main objective of this study is to analyze the relationship between the final result of soccer matches and the individual technical and tactical performances in a national team during the Copa America 2019. The study, characterized as a case study, had a sample of 20 athletes participating in the 6 official matches played by a national team during the Copa America 2019. For the collection of actions and tactical performances, it was used the Individual Tactical Behavior Assessment Protocol (DENIS, 2017), while the counting of technical actions was made through a scout using recorded images and made available by the Instat Football Scout platform. To verify the relationship between the results of the matches and the technical and tactical performances, descriptive, exploratory (independent t test and Spearman’s correlation) and multivariate (exploratory factor analysis and artificial neural network) analyzes were performed, using the SPSS 25.0 program and a significance level of 0.05. Significant differences were identified between the results in Offensive Time (t = 714.00; p = 0.001); Total Defensive Actions (t = 2.98; p = 0.001), Tactical Behavior Index (t = 332.00; p = 0.038), Defensive Actions Performed per Minute (t = 327.00; p = 0.032) and Actions Totals per Minute (t = 3.06; p = 0.003) and correlations between Passes with Penetration (r = 0.901; p <0.001) and with Offensive Coverage (r = 0.921 ; p <0.001), Passes Correct with Penetration (r = 0.897; p <0.001) and with Offensive Coverage (r = 0.915; p <0.001), Tackle with Delay (r = 0.352; p = 0.004) and Interceptions with Concentration (r = 0.471; p <0.001). By applying the exploratory factor analysis, it was possible to identify those 4 factors, with 22 variables, had the power to explain 61.8% of the proportion of variance and,with these variables applied to an artificial neural network, there was a prediction of 100% of the results. In this way, it is possible to recognize that there is a correlation between fundamental tactical principles and technical fundamentals and that there are variables with differences between matches with different results. It was also possible to identifying the variables that become more decisive for the result of the matches and for the performance of the athletes throughout the championships.